How Guilds Build Success; Aspects of Temporal Resource Partitioning in a Warm, Temperate Climate Assemblage of Dung Beetles (Coleoptera: Scarabaeidae). Issue 5 (19th July 2017) - Sullivan, Gregory T; Ozman-Sullivan, Sebahat K; Lumaret, Jean-Pierre; Bourne, Anne; Zeybekoglu, Unal; Zalucki, Myron P; Baxter, Greg
Abstract: Succession in local dung beetle assemblages influences their delivery of ecological functions in natural and modified environments globally. Short-term changes in dung beetle (Coleoptera: Scarabaeidae) species richness, abundance, and biomass were investigated in standardized dung pads in northern, coastal Turkey. For mean tunneling guild abundance, dung deposition time, dung exposure period, and their interaction were significant, and for mean dung dwelling guild abundance, dung exposure period was significant, as was the interaction with dung deposition time, which collectively evidenced temporal resource partitioning, based principally on differences in diel activity. Succession was highly compressed, with maximum abundance at 12h and maximum species richness at 24h. A large ball roller and small- to medium-sized tunnelers dominated different periods in the first 24h but were superseded by dwellers. Regression analysis demonstrated a significant, positive relationship between species richness and the evenness of abundance for both dung deposition times. Correlation analysis generally showed strong, positive correlations between tunneling species, low correlations between tunneling and dwelling species, and low correlations between dwelling species. Niche partitioning based on size difference appears to have acted on the environmental filtering of tunneling species along the temporal gradient of declining moisture, thereby limiting the number of abundant, concurrent species. The aggregation of tunneling species provided opportunities for the less competitive dwelling species to occupy less densely populated zones termed probability refuges. The network of strong, positive correlations between tunneling species may indicate that their collective functionality is vulnerable to loss of efficiency if species are lost.